Women’s Resilience and Survival Practices in Arundhati Roy’s The Ministry of Utmost Happiness - Yuliana Dwi Makhumah yuli; Arief Rahman Hakim (SINAU: Jurnal Ilmiah Pendidikan Dan Pembelajaran, 2025)
This study examines the representation of women's resilience in Arundhati Roy's The Ministry of Utmost Happiness (2017) through the framework of Feminist Literary Criticism. Focusing on two central characters Anjum, a hijra who establishes an alternative community in a Delhi graveyard, and Tilottama (Tilo), an enigmatic woman entangled in Kashmir's political violence.The analysis explores how women navigate conditions of marginalization and state violence through distinct survival practices Anjum's resilience emerges through care work, community-building, and spatial transformation, creating infrastructure that enables collective survival for the socially rejected. In contrast, Tilo's survival operates through affective withdrawal, strategic opacity, and bodily persistence, refusing normative emotional labor and maintaining protective distance even within intimate relationships. Drawing on contemporary feminist theory, this analysis demonstrates how Roy's novel challenges singular narratives of women's agency, presenting multiple modalities of survival suited to different circumstances and capacities. The findings contribute to feminist literary scholarship by illuminating how women's everyday actions, whether building rooms, offering care, maintaining silence, constitute politically significant survival strategies that resist erasure and assert presence within conditions designed to eliminate them.